Predicting Suicide Attacks Integrating Spatial, Temporal, and Social Features of Terrorist Attack Targets - Perry, Walter L. (RAND Corporation, 2013)
As part of an exploration of ways to predict what determines the targets of suicide attacks, RAND conducted a proof-of-principle analysis of whether adding sociocultural, political, economic, and demographic factors would enhance the predictive ability of a methodology that focused on geospatial features. This test case focused on terrorist bombing incidents in Israel, but the findings indicate that the methodology merits further exploration.